Synchrotron‐Based X‐ray Absorption Fine Structures, X‐ray Diffraction, and X‐ray Microscopy Techniques Applied in the Study of Lithium Secondary Batteries. Issue 8 (18th April 2018) - Li, Weihan; Li, Minsi; Hu, Yongfeng; Lu, Jun; Lushington, Andrew; Li, Ruying; Wu, Tianpin; Sham, Tsun‐Kong; Sun, Xueliang
Abstract: Owing to the recent advance of third‐generation synchrotron radiation (SR) sources, SR‐based X‐ray techniques have been widely applied to study lithium‐ion batteries, lithium–sulfur batteries, and lithium–oxygen batteries to solve material challenges. SR‐based techniques provide high chemical and physical sensitivity and a comprehensive picture of material structure and reaction mechanisms. An in‐depth understanding of batteries is imperative for the development of future energy storage devices with enhanced electrochemical performance to meet societies' growing need for devices with high energy density. Here, recent progress in the application of SR techniques for lithium secondary batteries with a focus on several techniques, including X‐ray absorption fine structure, synchrotron X‐ray diffraction, and synchrotron X‐ray microscopy techniques is reviewed. The working principle for all characterization techniques is introduced to provide context for how the technique is used in the field of energy storage. Through discussing the utilization of SR techniques in different directions of batteries, including electrodes, electrolytes, and interfaces, the practical application strategies of techniques in batteries are clarified. By summarizing and discussing the application of SR techniques in batteries, the aim is to highlight the crucial role of SR characterization in the development of advanced energy materials. Abstract : The recent progress in the application of synchrotron techniques for lithium secondary batteries with a focus on several techniques, including X‐ray absorption fine structure, synchrotron X‐ray diffraction, and synchrotron X‐ray microscopy techniques is summarized, highlighting the crucial role of synchrotron characterization in the development of advanced energy materials.